The impact of health expenditures on public health in BRICS nations - Jakovljevic, Mihajlo (J Sport Health Sci, 2019)
• Experiencing a rapid economic growth, Brazil, Russia, India, China, and South Africa (BRICS nations) are now confronting a growing aging population and an increasing prevalence of noncommunicable diseases. • The health care spending share of the economy in the BRICS nations is growing and constitutes an important part of governmental efforts to address population health and health care systems. • Even with the growth in health expenditures, there remains a significant challenge in balancing the need for promoting public health, controlling noncommunicable diseases, and improving population health in these emerging economies. • BRICS nations have a great potential for embracing a public health agenda aimed at promoting physical activity and healthy lifestyles as part of the BRICS public health policies in order to improve population health and reduce the burden of noncommunicable diseases.